Angka Kasus Kekerasan dalam Rumah Tangga di Kota Manado Tahun 2018-2019 - Tumewu, Rebennia; Tomuka, Djemi; Kristanto, Erwin G. (e-CliniC, 2021)
Abstract: Domestic violence is universal and can occur regardless of age, profession, economic level or education of the victims. According to World Health Organization, 1 in 3 women in the world had experienced physical or sexual violence. In addition, according to the British Crime Survey, 1/3 of victims of domestic violence were male. This study was aimed to obtain the number of domestic violence cases in Manado during 2018-2019. This was a retrospective and descriptive study with a cross-sectional design using secondary data of domestic violence case reports at Polresta Manado regarding domestic violence in Manado 2018-2019. The results showed that there were 111 cases of domestic violence in 2018-2019 in Manado. Most cases occurred at Sario District (14 cases; 13%) dominated by physical violence (78 cases; 70%), committed by male perpetrators (101 cases; 91%), husbands of the victims (101 cases; 91%), and age group of 15-24 years (43 cases; 39%). In conclusion, there was a fluctuation in the number of domestic violence cases; an increase of 51.3% comparing to the number of cases in 2012-2013 and a decrease of 27.4% comparing to the number of cases in 2015-2016.Keywords: domestic violenceÂ Abstrak: Kekerasan dalam rumah tangga (KDRT) merupakan hal yang universal dan dapat terjadi tanpa memandang usia, profesi, tingkat ekonomi, maupun pendidikan dari korban. Menurut data WHO (World Health Organization), 1 dari 3 perempuan di dunia pernah mengalami kekerasan fisik maupun seksual. Selain itu, menurut British Crime Survey, 1/3 korban KDRT ialah laki-laki. Â Penelitian ini bertujuan untuk mendapatkan angka kasus KDRT di Kota Manado tahun 2018-2019. Jenis penelitian ialah deskriptif retrospektif dengan desain potong lintang. Data sekunder yaitu laporan kasus KDRT di Polresta Manado mengenai KDRT di Kota Manado pada tahun 2018-2019. Hasil penelitian mendapatkan, kasus KDRT pada tahun 2018-2019 di Kota Manado berjumlah 111 kasus, paling banyak terjadi di Kecamatan Sario (14 kasus; 13%), didominasi oleh jenis kekerasan fisik (78 kasus; 70%), pelaku berjenis kelamin laki-laki (101 kasus; 91%), yang merupakan suami korban (101 kasus; 91%), dan paling sering dialami oleh kelompok usia 15-24 tahun (43 kasus; 39%). Simpulan penelitian ini ialah terdapat fluktuasi angka kasus KDRT dibandingkan jumlah kasus pada tahun 2012-2013 yaitu terjadi peningkatan sebanyak 51,3% dan terjadi penurunan 27,4% bila dibandingkan dengan jumlah kasus pada tahun 2015-2016.Kata kunci: kekerasan dalam rumah tangga (KDRT)